2021
DOI: 10.3390/ani11051395
|View full text |Cite
|
Sign up to set email alerts
|

One Health Approach: An Overview of Q Fever in Livestock, Wildlife and Humans in Asturias (Northwestern Spain)

Abstract: This study aimed to investigate the seroprevalence of C. burnetii in domestic ruminants, wild ungulates, as well as the current situation of Q fever in humans in a small region in northwestern Spain where a close contact at the wildlife–livestock–human interface exists, and information on C. burnetii infection is scarce. Seroprevalence of C. burnetii was 8.4% in sheep, 18.4% in cattle, and 24.4% in goats. Real-time PCR analysis of environmental samples collected in 25 livestock farms detected Coxiella DNA in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 33 publications
(57 reference statements)
3
18
0
Order By: Relevance
“…According to the world animal health information system (WAHIS) of OIE, C. burnetii is prevalent worldwide, with an exception in New Zealand. Ticks may also play a significant role [13,14]. In Pakistan, Q fever was detected in camels in 1955 for the first time.…”
Section: Introductionmentioning
confidence: 99%
“…According to the world animal health information system (WAHIS) of OIE, C. burnetii is prevalent worldwide, with an exception in New Zealand. Ticks may also play a significant role [13,14]. In Pakistan, Q fever was detected in camels in 1955 for the first time.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, studies on the occurrence of C. burnetii infection in small ruminants are limited in Spain, and their impact in sheep and goat abortions remains unclear. Seroprevalence studies in semi-extensive grazing systems have shown herd seroprevalence values of up to 74% for sheep and 45% for goats, with individual seroprevalence values of 8.4% in sheep and 24.4–42% in goats [ 35 , 36 , 37 ]. Likewise, C. burnetii seems to be a widespread pathogen in environmental samples collected in Spanish livestock farms, as documented by the high percentage of dust and/or aerosols samples (36–80%) testing positive by real-time PCR analyses [ 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…Seroprevalence studies in semi-extensive grazing systems have shown herd seroprevalence values of up to 74% for sheep and 45% for goats, with individual seroprevalence values of 8.4% in sheep and 24.4–42% in goats [ 35 , 36 , 37 ]. Likewise, C. burnetii seems to be a widespread pathogen in environmental samples collected in Spanish livestock farms, as documented by the high percentage of dust and/or aerosols samples (36–80%) testing positive by real-time PCR analyses [ 37 , 38 ]. In this study, the current status of C. burnetii infection and other major pathogens, causing abortion in sheep and goat flocks from Spain and Portugal, was investigated through cases submitted for diagnosis to a veterinary laboratory.…”
Section: Introductionmentioning
confidence: 99%
“…More than 50 different species—including wild and domestic ungulates (e.g., red deer, roe deer, fallow deer, chamois, mouflon, European bison, wild boar, sheep, goat, cattle), wild carnivores (e.g., wolf, Eurasian lynx, Eurasian badger, coypu, beech marten, golden jackal), micromammals (e.g., yellow-necked field mouse, long-tailed field mouse, European water vole, white-toothed shrew, garden dormouse, common vole, house mouse, western Mediterranean mouse, black rat, Eurasian red squirrel), non-human primates (the genera Cebuella, Cercocebus, Cercopithecus, Eulemur, Hylobates, Lemur, Macaca, Mandrillus, Saimiri, and Varecia ), turtles (e.g., Testudo hermanni , T. h. boettgeri , T. graeca , and T. marginata ), bats (the families Pteropodidae, Emballonuridae, Rhinolophidae, Hipposideridae, and Vespertilionidae), and ticks ( Ixodes ricinus , Dermacentor marginatus , Hyalomma marginatum )—are included. Regarding the zoonotic pathogens represented in this issue, the presence of or exposure to 17 different pathogens—including viruses [ 4 ] (West Nile virus), bacteria [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ] ( Anaplasma phagocytophilum, Coxiella burnetii, Helicobacter pylori, H. suis, Mycobacterium tuberculosis Complex, Salmonella sp., and Leptospira interrogans sensu stricto), and parasitic protists [ 14 , 15 ] (e.g., Cryptosporidium spp., Giardia duodenalis , Blastocystis sp., Enterocytozoon bieneusi , Entamoeba histolytica , Entamoeba dispar , Balantioides coli , Troglodytella spp., Leishmania spp. )—are presented.…”
mentioning
confidence: 99%
“…The authors additionally suggest that micromammals may be potential sources to trace back the origin of human Q fever and animal coxiellosis cases in Europe, and might be relevant in the maintenance of wild-type C. burnetii strains that can be a matter of concern for animal and human health authorities. Espí et al [ 8 ] investigated the seroprevalence of C. burnetii in domestic ruminants and wild ungulates, as well as the current situation of Q fever in humans, in a small region in northwestern Spain, where close contact at the wildlife–livestock–human interface exists, and information on C. burnetii infection is scarce. Seroprevalence of C. burnetii was 8.4% in sheep, 18.4% in cattle, and 24.4% in goats.…”
mentioning
confidence: 99%